Coffee and the risk of osteoarthritis: a two-sample, two-step multivariable Mendelian randomization study - Zhang, Wenzheng; Lei, Xuefeng; Tu, Yihui; Ma, Tong; Wen, Tao; Yang, Tao; Xue, Long; Ji, Jiazhong; Xue, Huaming (Frontiers in Genetics, 2024)
Purpose: To investigate the potential causal relationship between coffee consumption and osteoarthritis (OA), and to disentangle whether body mass index (BMI) and Bone mineral density (BMD) mediate this relationship.We performed two-sample and two-step Mendelian randomization (MR) analyses utilizing publicly available genome-wide association studies (GWAS) summary statistics to estimate the association between coffee intake and OA risk (including knee OA, hip OA, knee or hip OA, and total OA), as well as the possible mediating effects of BMI and BMD. In addition, data of different coffee types (decaffeinated coffee, instant coffee, ground coffee -including espresso, filter, etc., and other coffee types) were used to explore the effect of coffee type on the risk of OA.In two-sample MR, coffee intake increased the risk of OA in various sites, with the most significant impact observed in knee osteoarthritis (KOA) (odds ratio [OR] 2.03, 95% confidence interval [CI] 1.57-2.61, P<0.001). The effect on self-reported OA was minimal (OR 1.03, 95% CI 1.01-1.05, P=0.006). Further analysis of different types of coffee revealed that only decaffeinated coffee was causally associated with both KOA (OR 4.40, P=0.002) and selfreported OA (OR 1.13, 95% CI 1.02-1.26, P=0.022). In two-step MR, BMI explained over half of the coffee intake-all OA risk association, while BMD accounted for less than 5% of the mediation effect.Our study suggests that coffee intake increase the risk of OA, with BMI playing a significant mediating role. Decaffeinated coffee appears to have the greatest impact on OA risk compared to other types of coffee. Therefore, managing BMI and selecting appropriate types of coffee should be included in the health management of individuals who frequently consume coffee.